Quality improvement project identifies factors associated with delay in IBD diagnosis. Issue 3 (23rd June 2020) - Walker, Gareth J.; Lin, Simeng; Chanchlani, Neil; Thomas, Amanda; Hendy, Peter; Heerasing, Neel; Moore, Lucy; Green, Harry D.; Chee, Desmond; Bewshea, Claire; Mays, Joseph; Kennedy, Nicholas A.; et al.
Summary: Background: Delay in the diagnosis of inflammatory bowel disease (IBD) is common and contemporary UK studies are lacking. Aim: To determine factors associated with, and the consequences of, a prolonged time to diagnosis in IBD. Methods: This quality improvement study included 304 adults with a new IBD diagnosis made between January 2014 and December 2017 across 49 general practices (GP) and gastroenterology secondary care services. Outcome measures were demographic, clinical and laboratory factors associated with a delayed time, defined as greater than upper quartile, to: (a) patient presentation (b) GP referral (c) secondary care diagnosis, and factors associated with a complicated disease course (hospitalisation and/or surgery and/or biologic treatment) in the year after diagnosis. Results: The median [IQR] diagnosis sub‐intervals were: (a) patient = 2.1 months [0.9‐5.1]; (b) GP = 0.3 months [0.0‐0.9]; (c) secondary care = 1.1 months [0.5‐2.1]. 50% of patients were diagnosed within 4 months and 92% were diagnosed within 2 years of symptom onset. Diagnostic delay was more common in Crohn's disease (7.6 months [3.1‐15.0]) than ulcerative colitis (3.3 months [1.9‐7.3]) ( P  < 0.001). Patients who presented as an emergency ( P  < 0.001) but not those with a delayed overall time to diagnosis ( P  = 0.35) were more likely to have a complicated disease course. Conclusion: Time to patient presentation is the largest component of time to IBD diagnosis. Emergency presentation is common and, unlike a delayed time to diagnosis, is associated with a complicated disease course.